Analisis Disiplin Kerja Dalam Meningkatkan Kinerja Karyawan Pada Pt Cube Integrasi Media Jakarta Selatan - Hikmah Rizkita Putri; Dewi Sartika (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze work discipline in improving employee performance at PT Cube Integrasi Media, South Jakarta. The research used a descriptive qualitative approach with data collection techniques through in-depth interviews and Focus Group Discussions (FGD). The results show that work discipline in the company is for the influenced by effective and inspirational leadership, good communication between leaders and subordinates, consistent company policies with a fair reward and punishment system, employees’ personal awareness and commitment, and a positive work environment. Work discipline has been proven to improve work quality and quantity, operational efficiency, reduce work errors, enhance teamwork, and accelerate target achievement, thus creating sustainable company competitiveness. This study concludes that work discipline is an important element in supporting employee performance at PT Cube Integrasi Media, South Jakarta.